Management of the Sungai Peduli Movement Foundation in Implementing Green Da'wah in Percut Sei Tuan District - Ningsih, Putri Setia; Soiman, Soiman (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This research aims to delve into the management of Green Da'wah implementation, expound on the management process executed by the River Care Movement Foundation, and pinpoint factors influencing the success of Green Da'wah at the foundation. Employing a qualitative descriptive approach, the study was conducted at the Sungai Care Movement Foundation, situated in Deli Serdang Regency. Data collection involved observation, interviews, conversations, and documentation review. Findings indicate adherence to the P-O-A-C stages, emphasizing environmental awareness, empowerment, and spiritual formation. Enthusiastic volunteers, donor support, and community involvement are identified as supportive factors, while the lack of attention from policy makers towards environmental awareness poses a significant hindrance.